2018
DOI: 10.1007/s10266-018-0338-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a calcium chloride solution treatment on physical and mechanical properties of glass ionomer cements

Abstract: This paper details a novel method to improve wear resistance of dental glass ionomer cement (GIC) restorations. The purpose of this in vitro study was to evaluate the effect of a calcium chloride (CaCl) solution treatment on surface hardness, surface roughness, compressive strength, water sorption and solubility of three conventional glass ionomer cements (GICs). Additionally, the changes of the Ca composition and morphology of the surface of the tested GICs were also investigated. The experimental groups of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…By adopting an alpha (α) level of 0.05, a beta (β) of 0.2 (i.e. power=80%), and an effect size (d) of 1.32 calculated based on the results of a previous study [8] . The total sample size was 80 samples: 40 for Fuji IX group and 40 for Fuji II LC group.…”
Section: Sample Sizementioning
confidence: 99%
See 2 more Smart Citations
“…By adopting an alpha (α) level of 0.05, a beta (β) of 0.2 (i.e. power=80%), and an effect size (d) of 1.32 calculated based on the results of a previous study [8] . The total sample size was 80 samples: 40 for Fuji IX group and 40 for Fuji II LC group.…”
Section: Sample Sizementioning
confidence: 99%
“…For preparation of disk-shaped specimen measuring a specially designed custom-made split Teflon mold was fabricated with 7 mm diameter and 2 mm thickness with an external metallic ring. The assembled split Teflon mold within the metallic ring were placed over a polyester strip (0.05 mm thickness) on a glass slab [8] .…”
Section: Steps For Disk Shaped Specimens' Preparation For Both Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method of improving GIC setting reaction through the supply of Ca cations using a CaCl 2 solution is based on the fact that the main setting reaction of GICs is the cross-linking of the carboxylate groups of polyalkenoic acids with the Al 3+ and Ca 2+ ions released from glass particles. A significant increase in surface hardness of various GICs has been reported when this method is used [16,17,24,25]. Considering that surface hardness of a restorative material is important for its wear resistance, this increase may improve the longevity of the restoration in clinical conditions.…”
Section: Editorialmentioning
confidence: 99%
“…It has been found that surface hardness increase is significantly correlated with the concentration of Ca ions on the GIC's surface [17], the immersion time in the CaCl 2 solution [24] and the concentration of the solution [24]. A recent study [25] reported that immersion of GIC specimens into 10 ml of a 42.7 wt% CaCl 2 solution (saturated concentration of CaCl 2 solution at 20 o C) for 60 sec increased surface hardness (5.3 to 7%), and decreased water sorption (3.3-24.4%) and solubility (2.2-33.5%).…”
Section: Editorialmentioning
confidence: 99%